The first experience of a text-based role-playing game as a type of online class - Krishtafor , Daria; Kravets , Olha; Yekhalov , Vasyl; Ploshchenko , Yuliia; Pylypenko , Olha; Yehorova , Olha (The Ukrainian Scientific Medical Youth Journal, 2024)
the start of a large-scale invasion in Ukraine in 2022 made face-to-face attendance at educational institutions dangerous and not always possible, prompting a return to the remote form introduced in 2020 at the start of the COVID-19 pandemic. But in wartime, classes often have to be interrupted to go to shelters, and connection can be unstable. All this encourages the search for new methods of distance learning. The graduate doctors who were studying at the cycle of cardiopulmonary and cerebral resuscitation, were offered the format of a text role-playing game in the Telegram messenger chat. Conceptually, this format does not differ from in-person simulation scenarios: the professor gives the audience a scenario and, depending on their actions, describes the patient's reactions. The difference is that without access to the mannequin and without the opportunity to practice in real time, the doctors described their actions in text form. Three doctors participated in each scenario: one in the role of a "doctor" (team leader), two in the roles of "nurses". The role of the "doctor" involved medical manipulations, organizing the work of the team and delegating tasks to the "nurses", diagnosing and prescribing treatment. The role of the "nurse" involved carrying out the doctor's orders and reporting possible problems. The rest of the group watched as the script was worked out. When serious mistakes were made in the protocol, the teacher stopped the scenario and suggested that the whole group reflect and discuss whether everything was done correctly. The students had time to consult the lecture notes and clinical protocols. Through the discussion, the students themselves chose the correct option, after which the scenario continued. The doctors showed high motivation and interest in the class in this format. When returning to the classroom, those who participated in the role-play performed significantly better than those who had only read material on the topic and/or listened to a lecture. Only practical skills on the mannequin required correction. Our first experience with this format has shown that, if a simulation in the classroom is not available, a text-based role-play is a more effective form of learning than a traditional survey.